Flexible Formgebung von Blechen durch Laserstrahlumformen - Hennige, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2001)
The main aim of this work was to develop a basic understanding of the mechanisms and parameters of the laser forming process to characterise the potentials of laser forming for rapid prototyping and small series production tasks. In order to analyse the geometrical constraints of the spatial forming process, the transition from linear laser bending to spatial laser forming was investigated using transition geometries with curved irradiation paths. These investigations showed the strong influence of the geometrical induced strain hindrances during the expansion phase and the contraction phase of the laser irradiation. Based on these results an analysis of suitable irradiation patterns and the resulting shaping potential of laser forming was possible. An iterative production sequence for the generation of a spherical bowl using basic irradiation sequences, adaptive irradiation sequences for correcting the local geometrical deviations and intermediate measurement cycles showed the feasibility of controlled flexible shaping by laser forming. In addition, the laser induced changes of the microstructure and the mechanical properties of the material were analysed in order to finally enable the definition of optimised irradiation strategies for laser forming of sheet metal part